Clinicopathological and Immunohistochemical Analysis of 21 cases of Traumatic Ulcerative Granuloma with Stromal Eosinophilia Using CD30, CD68 and TGF-β1 - Mustafa B Al-Talqani; Bashar H Abdullah; Ameer D Hameedi (College of Dentistry/ University of Baghdad, 2018)
Background: Traumatic ulcerative granuloma with stromal eosinophilia is an impressive benign chronic ulcerative lesion of the oral mucosa with vague etiopathogenesis. It was supposed to represent an oral counterpart of primary cutaneous CD30+ lymphoproliferative disorder. Histopathologically, it is characterized by mixed inflammatory infiltrate predominated by histiocytes, lymphocytes and eosinophils along with presence of scattered large atypical mononuclear cells. It has worrisome clinical presentation. It may heal spontaneously, but in most occasions it persists and never heal unless removed surgically (incisional or excisional biopsy). A rare subset may show worrisome immunohistochemical features. Follow up is highly recommended. Materials and methods: Formalin fixed - paraffin embedded tissue blocks of twenty-one cases were cut and mounted on positively charged slides and stained by primary antibodies (CD30, CD68 and TGF-β1). A statistical analysis was performed between the immunohistochemical scores for markers with each other and with clinicopathological parameters (age, sex, size of ulcer, number of eosinophils and mitoses). Results: The age of the patients ranged from 20 to 72 years, with a higher female propensity. Immunohistochemical positive expression for CD30 (16 case) mainly involved round small lymphocytes, while all cases were positive for CD68 and TGF-β1. Statistically, there was no significant relation between the scores of CD30, CD68 and TGF-β1 with each other and with the aforementioned parameters, (P<0.05). The eosinophils count showed a significant positive correlation with age (P=0.008), size of ulcer (P=0.007) and mitoses (P=0.004). Conclusion: Traumatic ulcerative granuloma with stromal eosinophilia is a benign and reactive chronic oral ulcerative lesion rather than being CD30+ lymphoproliferative disorder; this conclusion is supported by heterogeneous, focal and nonspecific staining for CD30 and being typically infiltrated by CD68+ macrophages. Whereas, a high level of expression for TGF-β1 indicated that the aforementioned factor was not associated with the delayed healing of this lesion